Ilustrasi Digital Bergaya Semi-Realis sebagai Interpretasi Simbolis Lagu-Lagu Blink-182 - Galuh Prasasti; Bangkit Sanjaya (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Music functions not only as an auditory medium but also as a source of visual interpretation through the process of intersemiotic translation, which enables meanings expressed through lyrics and musical atmosphere to be translated into visual forms. This creative research aimed to produce semi-realistic digital illustrations as symbolic interpretations of three Blink-182 songs, namely "What's My Age Again?", "She's Out of Her Mind", and "One More Time", selected to represent different themes and phases in the band's musical career. The study employed a qualitative creation-based approach using thematic analysis to identify dominant themes, emotional atmospheres, and symbolic elements embedded in the song lyrics. The analytical findings were then transformed into visual metaphors through a creative process consisting of pre-production, production, and post-production stages using Adobe Illustrator with the gradient mesh technique to achieve a semi-realistic visual style. The creative outcomes comprise three digital illustrations entitled "Merry-Go-Nowhere", "B-Side Brain", and "Ghosted (By The Couch)", representing themes of adulthood crisis, irrational obsession in personal relationships, and regret over loss and the fleetingness of time without depicting the physical appearance or iconic attributes of the band members. The creation demonstrates that semi-realistic digital illustration effectively communicates the emotional meanings of song lyrics through symbolic visual representation while offering an alternative approach to music visualization that emphasizes personal interpretation, metaphorical expression, and visual storytelling. Furthermore, this study provides a practical reference for illustrators and visual communication designers in developing music-inspired visual works through symbolic interpretation.